Effect of Solid Particle Properties on Heat Transfer and Pressure Drop in Packed Duct - Hilal, Kifah H.; Omran, Salman H.; Abdulla, Muthanna L. (Al-Khwarizmi Engineering Journal, 2013)
This work examines numerically the effects of particle size, particle thermal conductivity and inlet velocity of forced convection heat transfer in uniformly heated packed duct. Four packing material (Aluminum, Alumina, Glass and Nylon) with range of thermal conductivity (from200 W/m.K for Aluminum to 0.23 W/m.K for Nylon), four particle diameters (1, 3, 5 and 7 cm), inlet velocity ( 0.07, 0.19 and 0.32 m/s) and constant heat flux ( 1000, 2000 and 3000 W/ m 2) were investigated. Results showed that heat transfer (average Nusselt number Nuav) increased with increasing packing conductivity; inlet velocity and heat flux, but decreased with increasing particle size.Also, Aluminum average Nusselt number is about (0.85,2.2 and 3.1 times) than Alumina, glass and Nylon respectively. From optimization between heat transfer and pressure drop through packed duct, it is found thatfinest ratio (Nuav / Δp) equal to (19.12) at (Dp = 7 cm, inlet velocity = 0.07 m/ s and 3000 W/m2 heat flux) with Aluminum as packing material.